Bloodbath nation - Auster, Paul, 1947- (Grove Press, 2023)
"Each year, approximately forty thousand Americans are killed by gunshot wounds, which is roughly equivalent to the annual rate of traffic deaths on American roads and highways. Of those forty thousand gun fatalities, more than half of them are suicides, which in turn account for half of all suicides per year. Add in the murders caused by guns, the accidental deaths caused by guns, the law enforcement killings caused by guns, and the average comes out to more than one hundred Americans killed by bullets every day. On that same average day, another two hundred-plus are wounded by guns, which translates into eighty thousand a year. Eighty thousand wounded and forty thousand dead, or one hundred and twenty thousand ambulance calls and emergency room cases for every twelve-month tick of the clock, but the toll of gun violence goes far beyond the pierced and bloodied bodies of the victims themselves, spilling out into the devastations visited upon their immediate families, their extended families, their friends, their fellow workers, the people of their neighborhoods, their schools, their churches, their softball teams, and communities at large-the vast brigade of lives touched by the presence of a single person who lives or has lived among them-meaning that the number of Americans directly or indirectly marked by gun violence every year must be tallied in the millions"--